(untitled) (Revisão de Sociologia Clínica, 2024)
This article discusses the significant contributions made by Wan Halim Othman in the advancement of clinical sociology in Malaysia. Wan Halim, introduced as the progenitor of Clinical Sociology in Malaysia, has played a pivotal role in social issue management and his unique approaches have had a lasting social impact in the country. This article starts with the backdrop of the country and the main figure - Wan Halim Othman, and then discusses the various innovative and impactful initiatives that he has spearheaded using the clinical sociology approach. Programmes such as PINTAS and the social clinic exemplify the profound capacity of clinical sociology to address intricate societal issues. Wan Halim has effectively empowered marginalized communities and promoted social cohesion by implementing new strategies, like community mediation and support groups specifically designed for single moms. Though clinical sociology is gaining traction in Malaysia, much needed to be done to further recognize and institutionalize this discipline. Among the proposed next steps include the formalization of clinical sociology by implementing comprehensive curricula, hands-on training, and professional certification. The author emphasizes the significance of fostering collaboration among academia, government, and civil society in order to establish clinical sociology as an institutionalized field and effectively tackle urgent societal issues.